Fibrinogen Chains Intrinsic to the Brain - Golanov, Eugene V.; Sharpe, Martyn A.; Regnier-Golanov, Angelique S.; Del Zoppo, Gregory J.; Baskin, David S.; Britz, Gavin W. (Frontiers in Neuroscience, 2019)
We observed fine fibrin deposition along the paravascular spaces in naive animals, which increased dramatically following subarachnoid hemorrhage (SAH). Following SAH, fibrin deposits in the areas remote from the hemorrhage. Traditionally it is thought that fibrinogen enters subarachnoid space through damaged blood brain barrier. However, deposition of fibrin remotely from hemorrhage suggests that fibrinogen chains Aα, Bβ and  can originate in the brain. Here we demonstrate in vivo and in vitro that astroglia and neurons are capable of expression of fibrinogen chains. SAH in mice was induced by the filament perforation of the circle of Willis. Four days after SAH animals were anesthetized, transcardially perfused and fixed. Whole brain was processed for immunofluorescent (IF) analysis of fibrin deposition on the brain surface or in brains slices processed for fibrinogen chains Aα, Bβ,  immunohistochemical detection. Normal human astrocytes were grown media to confluency and stimulated with NOC-18 (100 μM), TNF-α (100 nM), ATP--S (100 µM) for 24 hours. Culture was fixed and washed/permeabilized with 0.1% Triton and processed for IF. Four days following SAH fibrinogen chains Aα IF associated with glia limitans and superficial brain layers increased 3.2 and 2.5 times (p<0.05 and p<0.01) on the ventral and dorsal brain surfaces respectively; fibrinogen chains Bβ increased by 3 times (p<0.01) on the dorsal surface and fibrinogen chain  increased by 3 times (p<0.01) on the ventral surface compared to sham animals. Human cultured astrocytes and neurons constitutively expressed all three fibrinogen chains. Their expression changed differentially when exposed for 24 hours to biologically significant stimuli: TNFα, NO or ATP. Western blot and RT-qPCR confirmed presence of the products of the appropriate molecular weight and respective mRNA. We demonstrate for the first time that mouse and human astrocytes and neurons express fibrinogen chains suggesting potential presence of endogenous to the brain fibrinogen chains differentially changing to biologically significant stimuli. SAH is followed by increased expression of fibrinogen chains associated with glia limitans remote from the hemorrhage. We conclude that brain astrocytes and neurons are capable of production of fibrinogen chains, which may be involved in various normal and pathological processes.